Treating perfectionism using internet-based cognitive behavior therapy: A study protocol for a randomized controlled trial comparing two types of treatment - Monica Buhrman; Olle Gelberg; Filip Jovicic; Katarina Molin; David Forsström; Gerhard Andersson; Per Carlbring; Roz Shafran; Alexander Rozental (Internet Interventions, 2020)
Perfectionism is characterized by setting high standards and striving for achievement, sometimes at the expense of social relationships and wellbeing. Despite sometimes being viewed as a positive feature by others, people with perfectionism tend to be overly concerned about their performance and how they are being perceived by people around them. This tends to create inflexible standards, cognitive biases, and performance-related behaviors that maintain a belief that self-worth is linked to accomplishments. Cognitive behavior therapy has been shown to be a viable treatment for perfectionism, both in terms of reducing levels of perfectionism and improving psychiatric symptoms. Furthermore, a number of recent studies indicate that it can be successfully delivered via the Internet, both with regular support and guidance on demand from a therapist. In the present study protocol, a clinical trial for perfectionism is described and outlined. In total, 128 participants will be recruited and randomized to either a treatment that has already been demonstrated to have many benefits, Internet-based Cognitive Behavior Therapy for perfectionism (iCBT-P), or an active comparison condition, Internet-based Unified Protocol (iUP), targeting the emotions underlying depression and anxiety disorders. The results will be investigated with regard to self-reported outcomes of perfectionism, psychiatric symptoms, self-compassion, and quality of life, at post-treatment and at six- and 12-month follow-up. Both iCBT-P and iUP are expected to have a positive impact, but the difference between the two conditions in terms of their specific effects and adherence are currently unknown and will be explored. The clinical trial is believed to lead to a better understanding of how perfectionism can be treated and the specificity of different treatments.